GAMBARAN KONSEP DIRI BAPAK RUMAH TANGGA - Della Della; Weny Savitry S. Pandia; Arafani Saezarina (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2018)
The amount of stay-at-home dad is increasing, although it is still considered as something unusual especially in traditional gender roles and patrilineal culture. Stay-at-home dad is a man who is married, does not work, works part time, or works by owning his own business, who chooses to be the primary caregiver of his children and spends a minimum of six hours per day for interacting with his children. Self-concept is an individual's self-image of beliefs that shape one's own nature. The aim of this qualitative study is to make an objective description about self concept of stay-at-home dads. Data was collected from three main subjects whom are in early adulthood and three triangulation subjecs, using an interview guidelines based on Fitts’ theory of self concept. Result shows that the self concept of stay-at-home dads have positive sides, especially in physical, moral-ethics, and family dimensions of self-concept, and negative sides, especially in personal and social dimensions of self-concept.